Asymmetric combinational "metal-biocatalytic system": One approach to chiral 2-subsituted-tetrahydroquinoline-4-ols towards two-step one-pot processes in aqueous media. Issue 23 (7th June 2017) - Wang, Juxiang; Li, Ke; Zhou, Xiaojian; Han, Wenyong; Wan, Nanwei; Cui, Baodong; Wang, Huihui; Yuan, Weicheng; Chen, Yongzheng
Graphical abstract: Highlights: Asymmetric "metal-biocatalytic system". One-pot conversion of 2-subsituted-quinolines to 2-subsituted-tetrahydroquinoline-4-ols. Synthesis of chiral 2-subsituted-tetrahydroquinoline-4-ols in moderate to excellent results. Further illustrates the potentiality of chemoenzymatic multistep one-pot processes. Abstract: A novel asymmetric "metal-biocatalytic system", involving Rh-catalyzed asymmetric transfer hydrogenation and whole cell mediated asymmetric hydroxylation in aqueous buffer, has been achieved. The methodology gives access to 2-subsituted-tetrahydroquinoline-4-ols bearing two stereocenters from 2-subsituted-quinolines in moderate to excellent results (up to 47% yield, 99:1 dr, and >99% ee).